A new species of Deltamys Thomas, 1917 (Rodentia: Cricetidae) endemic to the southern Brazilian Araucaria Forest and notes on the expanded phylogeographic scenario of D. kempi - Quintela, Fernando Marques; Bertuol, Fabrício; González, Enrique Manuel; Cordeiro-Estrela, Pedro; de Freitas, Thales Renato Ochotorena; Gonçalves, Gislene Lopes (Zootaxa, 2017)
Deltamys is a monotypic sigmodontine rodent from the Pampas of South America. In addition to the formally recognized D. kempi that inhabits lowlands, an undescribed form Deltamys sp. 2n=40 was recently found in the highlands of southeastern Brazil. In the present study, we perform a phylogeographic reassessment of Deltamys and describe a third form of the genus, endemic to the Brazilian Araucaria Forest. We describe this new species based on an integrative analysis, using complete cytochrome b DNA sequences, karyology and morphology. Bayesian tree recovered two allopatric clades (lowlands vs. highlands) and three lineages: (i) the lowland D. kempi, (ii) the highland Deltamys sp. 2n=40, and (iii) Deltamys araucaria sp. n. Deltamys araucaria sp. n. is karyotypically (2n=34) and morphologically distinguishable from D. kempi (2n=37-38), showing a tawnier dorsum/flank pelage, presence of a protostyle, M1 alveolus positioned anteriorly to the posterior margin of the zygomatic plate, and several other distinguishing characteristics. A phylogeographic assessment of D. kempi recovered two haplogroups with significant differences in skull measurements. This phylogeographic break seems to have been shaped by the Patos Lagoon estuarine channel. The diversification in Deltamys might have been triggered by dispersal of older lineages over different altitudinal ranges in the Paraná geological basin.